REAL-TIME DELPHI SURVEY ON COMPETITION AND COMPETITIVENESS OF GEOGRAPHICAL INDICATIONS AS A NEGOTIATIONS&APOS; ISSUE OF THE TRANSATLANTIC TRADE AND INVESTMENT PARTNERSHIP - Mariusz Maciejczak (Acta Scientiarum Polonorum. Oeconomia, 2016)
This paper aimed to present the issues of geographic indications as an element of the intellectual property right negotiations under the Transatlantic Trade and Investment Partnership between the European Union and the United States. It is argued that implementation of different legal regimes related to intellectual property might create significant barriers to the liberalization of international trade of quality food products. Using the results of foresight researches it was shown that the agreement might add small value to the development of markets and their participants in both regions. If is forth seen the possible positive impact with regard to competitive advantages of EU products and negative to EU market competition, and contrariwise, negative influence on competitive advantages of US products and positive on US market competition.